PENGEMBANGAN PERANGKAT PEMBELAJARAN TEORI EVOLUSI MELALUI MODEL DICK & CAREY BERBASIS PENDIDIKAN KARAKTER TERHADAP HASIL BELAJAR DAN SIKAP MAHASISWA BIOLOGI DI KOTA MALANG - Riyanto Riyanto; Numala Hindun (Universitas PGRI Madiun, 2014)
This research is to improve understanding of the concept and attitude on the phenomenon that is occurred, so as to understand the concept of the theory of evolution truelly with the next character-based on education is able to avoid misconception of the concept of evolution, which is still a matter of controversy .The experimental data is analyzed with analysis of covariance ( Anacova ), where the pre-test as a covariate, then further testing is done with a different test Least Significances Different ( LSD ). The statistical analysisis assisted by software of SPSS 14 for Windows, conducted with a significance level of 0.05 ( p< 0,05 ) .The Results of Anacova test showed that the Instructional Materials Theory of Evolution with Model Dick & Carey has real significant effect on cognitive achievement with calculation F value of 32. 014 with a value of p = 0.000 is smaller than the alpha value 0.05 which means that the null hypothesisis rejected and the research hypothesisis accepted which states there is influence teaching materials with on Theory of Evolution with Dick & Carey Model of the students’ cognitive achievement and the influence of Instructional Materials of Theory of Evolution by Dick & Carey Model on the attitude result indicates that calculation F value of 40.873 with a value of p = 0.000 is smaller than the alpha value of 0.05 which means that the null hypothesisis rejected and the research hypothesisis accepted which states there is the effect of different device Instructional Materials of Theory of Evolution by Dick & Carey Model for attitude learning outcomes.